Integration of Human Development and Financial Inclusion across Indian States - Dr. Raj Bihari Lal Srivastava (International Journal of Engineering and Management Research, 2020)
In this study, we look into the relationship between financial inclusion and economic growth in India. Secondary sources were used for this study. Research is conducted throughout 2019. Here, we examine the status of financial inclusion across 28 of India's states. The findings imply that most states have a very low degree of financial inclusion, and further study indicates a direct association of financial inclusion with growth and standard of life, and an inverse relation with poverty. Working on this problem led us to discover a beneficial Pearson's r illustrates a positive relationship between financial inclusion and GDP per capita. As a result, financial inclusion promotes economic development by increasing people's access to and use of formal financial systems, which helps advance human development. On top of that, it helps the Indian economy grow.